Self-similar pressure-atomized sprays. (25th April 2020) - Hinterbichler, H.; Steiner, H.; Brenn, G.
Abstract : Abstract : Sprays produced by pressure atomization of various liquids are investigated experimentally, showing the self-similar flow fields of both the liquid and the gas phases. Phase-Doppler measurements are conducted in the sprays at varying radial and axial distances from the atomizer orifice. The theoretical description of the gas flow field based on boundary-layer theory reveals a self-similar velocity field driven by momentum transfer from the liquid phase ejected into the gaseous environment. The momentum loss of the liquid droplet phase is also found to be self-similar, which was to be expected, but not shown in the literature before. The analytical self-similar description of the two-phase flow field is in excellent agreement with the experimental data.